The encyclopedia of deafness and hearing disorders - Turkington, Carol; Sussman, Allen E. (New York : Facts On File, 2004)
The Encyclopedia of Deafness and Hearing Disorders provides the most comprehensive source of information available about hearing impairment, as well as about treatments, noted specialists, and helpful organizations. More than 600 entries explain both the physical and psychological effects of living with hearing loss, in nonclinical language that is easy to understand. Topics include: degrees of hearing loss, from slight impairment to complete deafness; Edward Miner Gallaudet, who established the first college for deaf students in 1857; types of hearing aids and how they work; legal rights for the hearing impaired, including the Vocational Education Act of 1963; treatments for hearing loss in both children and adults; and organizations, such as the National Institute on Deafness and Other Communication Disorders.
Includes bibliographical references (p. 263-271) and index.
Keywords: Deafness -- Encyclopedias; Ear -- Diseases -- Encyclopedias; Hearing disorders -- Encyclopedias -- English